Penerapan Konsep Religious Culture dalam Menumbuhkan Keberagamaan Siswa - Iro Waziroh; St. Shofiyah (Kependidikan Islam Fakultas Agama Islam, 2023)
Education Islamic Religious Education is crucial in life; hence, an educator must be able to explain and present content effectively. Choose strategies and techniques based on the qualities and requirements of pupils, particularly children with special needs, particularly the deaf. The learning strategy for Islamic Religious Education for deaf children with special needs at SLB Tunas Bangsa Asembagus Situbondo uses an expository learning strategy, namely the delivery of material verbally from a teacher to a group of students and mastery of the material, in learning activities and holds learning preceded by preparation, presentation (delivering) material, correlation, concluding, and applying. The supporting factors in learning Islamic Religious Education are (1) internal factors, which include students' enthusiasm for studying and motivation. (2) external factors, namely the development of a harmonious connection between instructors and students, as well as between teachers and parents.